2021
DOI: 10.3846/jeelm.2021.15762
|View full text |Cite|
|
Sign up to set email alerts
|

Bioremediation of Chromium (Vi) by a Microbial Consortium Isolated From Tannery Effluents and Their Potential Industrial Application

Abstract: West Bengal has several leather industries and as such huge amount of leather are processed every year. The tannery effluents are discharged into the land and open water causing soil and water pollution respectively. Chromium is one of the most toxic inorganic contaminants which is well known for its carcinogenicity. Thus, our study focuses on investigating the bioremediation potential of common microflora isolated from tannery wastewater. In our study, Isolate 1 has the highest ability to reduce chromium (Cr6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…Study by Bhattacharjee et al showed the proficiency of Brevibacillus brevis US575 in reducing Cr 6+ to Cr 3+ [14]. The bacteria isolated from water samples were subjected to serial dilution technique in dilutions ranging from 10 -1 to 10 -4 .…”
Section: Previous Workmentioning
confidence: 99%
See 2 more Smart Citations
“…Study by Bhattacharjee et al showed the proficiency of Brevibacillus brevis US575 in reducing Cr 6+ to Cr 3+ [14]. The bacteria isolated from water samples were subjected to serial dilution technique in dilutions ranging from 10 -1 to 10 -4 .…”
Section: Previous Workmentioning
confidence: 99%
“…All the four colonies were taken and sub-cultured separately to obtain further pure cultures. Results by Bhattacharjee et al, have also demonstrated the ability of Brevibacillus brevis US575 in degrading leather [14]. Thus this isolate was taken for preparing biomass and to understand its adsorption isotherms, amongst which the authors have adopted the Langmuir and Freundlich isotherms.…”
Section: Previous Workmentioning
confidence: 99%
See 1 more Smart Citation